Dynamics and Control of Human Papillomavirus (HPV) Infection Using an SVITR Compartmental Model - MATONDO MANANGA, Herman; Lea-Irène, Milolo Kanumuambidi; Patience, Pokuaa Gambrah; Junior, Mukinayi Kanumuambidi; Marcial, Nguemfouo; Peter, Kasende Mundeke; Benjamin, Consolant Majegeza (Politeknik Negeri Batam, 2026)
Human papillomavirus (HPV) remains a significant public health concern due to its high transmissibility and associated health risks. This study underscores the pivotal role of vaccination in reducing HPV transmission, while also highlighting the limitations of relying solely on vaccination for infection control. In this study, we present a deterministic compartmental model to investigate the transmission dynamics of Human Papillomavirus (HPV). The model stratifies the population into five compartments: susceptible individuals S(t), Vaccinated individuals V(t), HPV Infected individuals I(t), treated HPV-infected individuals T(t) and recovered individuals R(t). We establish the existence and uniqueness of the model solution and also examine the existence of disease-free and endemic equilibrium and analyze their stability properties. Numerical simulations were performed to explore the temporal evolution of the compartments, assess the sensitivity of key parameters, and investigated the behaviour of the basic reproduction number R_0. Our findings were that a comprehensive strategy, incorporating both preventive vaccination and therapeutic management, is essential for achieving sustainable control of HPV spread. Strengthening these measures, alongside reducing transmission through demographic interventions, offers the best way for long-term management of the infection. These results provide insights into the impact of vaccination and treatment strategies on HPV transmission and highlight critical factors for public health.